Potential Impact of Atelectasis and Primary Tumor Glycolysis on F-18 FDG PET/CT on Survival in Lung Cancer Patients - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: Atelectasis is an important prognostic factor that can cause pleuritic chest pain, coughing or dyspnea, and even may be a cause of death. In this study, we aimed to investigate the potential impact of atelectasis and PET parameters on survival and the relation between atelectasis and PET parameters. Materials and Methods: The study consisted of patients with lung cancer with or without atelectasis who underwent F-18-FDG PET/CT examination before receiving any treatment. F-18-FDG PET/CT derived parameters including tumor size, SUVmax, SUVmean, MTV, total lesion glycosis (TLG), SUV mean of atelectasis area, atelectasis volume, and histological and TNM stage were considered as potential prognostic factors for overall survival. Results: Fifty consecutive lung cancer patients (22 patients with atelectasis and 28 patients without atelectasis, median age of 65 years) were evaluated in the present study. There was no relationship between tumor size and presence or absence of atelectasis, nor between presence/absence of atelectasis and TLG of primary tumors. The overall one-year survival rate was 83% and median survival was 20 months (n=22) in the presence of atelectasis; the overall one-year survival rate was 65.7% (n=28) and median survival was 16 months (p=0.138) in the absence of atelectasis. With respect to PFS; the one-year survival rate of AT+ patients was 81.8% and median survival was 19 months; the one-year survival rate of AT- patients was 64.3% and median survival was 16 months (p=0.159). According to univariate analysis, MTV, TLG and tumor size were significant risk factors for PFS and OS (p<0.05). However, SUVmax was not a significant factor for PFS and OS (p>0.05). Conclusions: The present study suggested that total lesion glycolysis and metabolic tumor volume were important predictors of survival in lung cancer patients, in contrast to SUVmax. In addition, having a segmental lung atelectasis seems not to be a significant factor on survival.
Keywords: Atelectasis; lung cancer; F-18-FDG; PET/CT; total lesion glycolysis; TOTAL LESION GLYCOLYSIS; PROGNOSTIC-SIGNIFICANCE; 18F-FDG PET/CT; CARCINOMA; VOLUME; CT; RADIOTHERAPY; THERAPY; BURDEN